Supervisi Pembelajaran Sebagai Pengembangan Budaya Mutu Guru - Rifa'i, Andi Arif (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2018)
The teacher is educator who has advantages as well as limitations as ordinary humans. Therefore he needs other people (supervisor) to help him minimize his weaknesses, so that his professional abilities are formed. In addition, supervision activitiy also aim to guarantee the quality of learning that has an impact on the quality of graduates. This means that supervision serves as a quality assurance aimed at establishing quality culture of teacher. Teachers with a high quality culture will lead to the achievement of the quality of learning and education and determine the quality and competitiveness of graduates.